Modelo paramétrico para extensão de deflúvios mensais - Lima, José Marcelo de Almeida (1974)
A parametric model for extension of short-term monthly streamflow data using monthly precipitation data of a set of stations inside the basin with longer record is presented. The model oriented to digital computation consists of two parts: one for self-optimization of the parameters, and another for extension of the records. Parameter sensitivity tests were carried on in order to check their final variation when poorly evaluated in the start of the self-optimization process. The model was appplied to the Alto Tietê basin in Pirapora, São Paulo state, with a drainage area of 5815 km2.